Evaluation of the effect of different immunomodulators against DT vaccine response - Ibtehal Hesham Hafez Amin; Amal Emad Eldin; Magdy Ali Amin; Osama Abdelwahid Hady (Cairo : Ibtehal Hesham Hafez Amin, 2016)
Diphtheria tetanus vaccine (DT) is a biological preparation of diphtheria and tetanus toxoids that provides immunity against corynebacterium diphtheriae and clostridium tetani. Immunomodulators could modulate the immune system response. This study aimed to evaluate the effect of glucan and nigella sativa oil (NSO) as immunomodulators on diphtheria tetanus vaccine. Mice were immunized by diphtheria and tetanus vaccine. Glucan or NSO were administered at different concentrations either alone or concurrent with the DT vaccine. The concentration of tetanus antibodies, diphtheria antibodies, IL-2 and IL-4 were determined by ELISA on days 15 and 28. Complete blood pictures were also determined on day 28. The concentration of anti-Tetanus antibodies and diphtheria antibodies were significantly increased by the administration of glucan at dose of 0.5 mg (P value 0.0 and 0.001 respectively). On the other hand, administration of NSO didn't significantly affect the levels of tetanus or diphtheria antibodies. IL-4 cytokine was significantly increased by the administration of 0.1 mg or 1 mg glucan (P value 0.025 and 0.000 respectively). IL-2 cytokine significantly increased by the administration of 1 mg glucan (P value 0.047). White blood cells and red blood cells count were significantly increased by the administration of glucan (P value 0.003 and 0.033 respectively), while only PLTs count were significantly increased by NSO (P value 0.024). Concurrent administration of glucan and DT vaccine significantly increased the WBCs, RBCs and PLTs count, while concurrent administration of NSO and DT vaccine did not significantly affect WBCs, RBCs or PLTs count. This study highlights the effect of immune enhancers on improving the host immune response to DT vaccine
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: DT; Immunomodulators against; Vaccine response